Catalytic cracking of wax esters extracted from Euglena gracilis for hydrocarbon fuel production. (May 2018) - Shimada, Iori; Nakamura, Yoshitaka; Kato, Shin; Mori, Ryohei; Ohta, Haruhisa; Suzuki, Kengo; Takatsuka, Toru
Abstract: Wax esters (WEs) synthesized by Euglena gracilis are potential sources for alternative fuels because of their high productivity, recent success in mass cultivation, and low energy consumption in extraction. In this study, deoxygenation of Euglena WE and conversion to hydrocarbons in a catalytic cracking process under a hydrogen-free atmosphere was investigated using a residue fluid catalytic cracking equilibrium catalyst with enhanced hydrogen-transfer activity. The deoxygenation of Euglena WE proceeded more rapidly with higher H2 O selectivity than that of saturated triglycerides. This is because initial β-elimination of WEs produces saturated fatty acids and higher olefins; the higher olefins rapidly release hydrogen species during cracking, cyclization and aromatization, and the hydrogen species accelerate hydrodeoxygenation of the saturated fatty acids. Furthermore, the cracking of Euglena WE produced large amounts of paraffins and olefins instead of aromatics. Therefore, Euglena WE was confirmed to be a preferable feedstock for the catalytic cracking process for hydrocarbon fuel production. Graphical abstract: Highlights: Conversion of Euglena wax ester to hydrocarbons in a catalytic cracking process. Rapid deoxygenation with high H2 O selectivity even under a H2 -free atmosphere. Large amounts of paraffins and olefins were produced rather than aromatics. Initial β-elimination produce highly reactive olefins that release hydrogen species. Hydrogen-transfer accelerates hydrodeoxygenation under a H2 -free atmosphere.